Selective potentiation of alpha 1 glycine receptors by ginkgolic acid - Maleeva, Galyna; Buldakova, Svetlana; Bregestovski, Piotr (Frontiers in Molecular Neuroscience, 2015)
Glycine receptors (GlyRs) belong to the superfamily of pentameric cys-loop receptor-operated channels and are involved in numerous physiological functions, including movement, vision and pain. In search for compounds performing subunit-specific modulation of GlyRs we studied action of ginkgolic acid, an abundant Ginkgo biloba product. Using patch-clamp recordings, we analysed the effects of ginkgolic acid in concentrations from 30nM to 25µM on α1- α3 and α1/β configurations of GlyR and on GABAARs expressed in cultured CHO-K1 cells and mouse neuroblastoma (N2a) cells. Ginkgolic acid caused an increase in the amplitude of currents mediated by homomeric α1 and heteromeric α1/β GlyRs and provoked a left-shift of the concentration-dependent curves for glycine. Even at high concentrations (10-25 µM) ginkgolic acid was not able to augment ionic currents mediated by α2 and α3 GlyRs, or by GABAAR consisting of α1/β2/γ2 subunits. Mutation of three residues (T59A/A261G/A303S) in the α2 GlyR subunit to the corresponding ones from the α1 converted the action of ginkgolic acid to potentiation with a distinct decrease in EC50 for glycine, suggesting an important role for these residues in modulation by ginkgolic acid. Our results suggest that ginkgolic acid is a novel selective enhancer of α1 GlyRs